The roles of Environmental Quality Act, Department of Environment and judges in the prevention of environmental pollution in Malaysia / Nahzatul Ain Mohd Khalid - Nahzatul Ain , Mohd Khalid (2004)
This dissertation attempts o examine the effectiveness of the roles playe by the Environmental Quality Act, the Department of Environment and he Jud1c1ary in the prevention of environmental pollution in Malaysia It firs outlines the concept of environmen, t, environmental pollut1on,environmental law, sources and consequences of en ironmental pollution. One of the main focus of his dissertation is to assess he Environmental Quality Act 1974 and to discuss it's implementation problems in he background of constitutional provisions.